Pengaruh Kepemimpinan Gembala Sidang terhadap Motivasi Pelayanan Kaum Awam - Elliya Dece (Sekolah Tinggi Teologi Real Batam, 2019)
Pastors and church leaders work as partner with the people of church in order to build God’s kingdom on earth. In reality, not all members of church are willing to participate in this service voluntarily. Paying attention to the strategic role of people in the church's development efforts, the attention of the leader in empowering church members needs to be done seriously so that church members can carry out their roles optimally in the life and work of the church. The hypothesis proposed in this study is that there is a significant influence between the pastor's leadership and the service motivation among the church members. The samples of this study are the GMI Baithani and GMI Efrata members, taken by random sampling technique. Data processing was assisted with SPSS 18 for Windows. The result of regression analysis of pastor’s leadership has significant effect to the service motivation of church members equal to 57% while 43% influenced by other factor.